Soundscape and fish passive acoustic monitoring around a North Sea gas-production platform in the Dogger Bank. - Marta Bolgan; Shireen J Bhalla; Ian Boyer Todd; Victoria L G Todd (PLoS ONE)
This study provides temporo-spatial characterisation of the underwater soundscape in proximity of a relatively newly installed offshore gas-production platform in the North Sea's Dogger Bank Special Area of Conservation, recorded by Static Acoustic Monitoring at different distances from the wellhead (70 m, 5 Km and 10 km). Long-Term Spectrogram Analysis and percentile Power Spectral Densities demonstrated strong acoustic similarity between sites; no biophonic acoustic-mass phenomena were present. All locations were characterized by Underwater Radiated Noise, concentrated < 2 kHz, which dominated the soundscape. Fish acoustic community analysis was performed to explore occurrence, richness, abundance, diel, and seasonal patterns of putative fish sounds. Principal Component Analysis was used to infer potential sound-emitting species, and was performed on North Sea fish sounds downloaded from the Global Inventory of known fish sounds (https://fishsounds.net/), analyzed for the same acoustic features used to characterize fish sounds recorded during this study. The fish acoustic community was characterized by low levels of diversity (acoustic richness ranging from 1 to 2) and abundance (never above 2 sounds min-1). The fish sound type 'Pulse Series' (PS), emitted at the 70 m and at the 5 km station in low abundance in September from ca. 19:00 to 23:00, was characterized by acoustic features with the closest linear combination to those typifying sounds emitted by Eutrigla gurnardus. The fish sound type 'Low-frequency Down-Sweep' (LF-DS) was recorded at all stations and was characterized by acoustic features with the closest linear combination to those typifying grunts emitted by Gadus morhua. This study represents the first application of fish acoustic community analysis in the context of environmental management of an operational offshore gas production platform.